Digging deeper into supply risk: a systematic literature review on price risks. Issue 5 (2nd September 2014) - Fischl, Maria; Scherrer-Rathje, Maike; Friedli, Thomas
Abstract : Purpose: – The purpose of this paper is both to provide an overview of existing knowledge pertaining to the management of price risks in manufacturing companies from an operations management (OM) perspective and to establish an agenda for future research. Risks related to the purchase prices of industrial consumption factors (raw materials, semi-finished/finished goods, auxiliary materials and operating materials) exert an increasing influence on manufacturing companies' business continuity and economic sustainability. Design/methodology/approach: – A systematic literature review was conducted following the literature search approach of vom Brocke et al. (2009). In total, 138 relevant articles were identified, analysed and synthesised. Findings: – The literature review reveals that the existing OM literature devotes little attention to price risks and their management in manufacturing companies. In particular, further empirical investigation is required to support decision-making in various risk contexts. Social implications: – This paper emphasises that in addition to existing national resource funds and inter-company alliances, alternative concepts are required to secure both stable prices and access to natural resources. Otherwise, in the future, small- and medium-sized companies, along with companies based in countries lacking available resource funds, will not have an opportunity to engage in fair competition. Originality/value: – To the best of the authors' knowledge, this is the first literature review to focus on price as a specific supply risk.